2009
DOI: 10.1111/j.1467-9663.2008.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Provision and Firm Location in Ohio: An Exploratory Spatial Analysis

Abstract: Information and communication technologies (ICTs) are often cited as an important factor in firm location decisions. This is especially true for firms engaged in information intensive activities and those that have a strong need for advanced services such as broadband. Despite the suggested importance of these technologies, quantitative work evaluating the link between firm location and broadband provision is sparse and existing knowledge remains largely theoretical and speculative. However, theoretical evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 49 publications
1
46
0
1
Order By: Relevance
“…The employees of these firms are also likely to be highly educated and highly technologically savvy to the extent that they consume a wide variety of digital services themselves. Mack & Grubesic (2009) identified that information, finance & insurance, and professional, scientific and technical employment are highly correlated with broadband provision. A statistically significant relationship exists between broadband and establishments, but the intensity of this depends on firm size and industry.…”
Section: Fixed and Mobile Ict Infrastructure In Contextmentioning
confidence: 99%
“…The employees of these firms are also likely to be highly educated and highly technologically savvy to the extent that they consume a wide variety of digital services themselves. Mack & Grubesic (2009) identified that information, finance & insurance, and professional, scientific and technical employment are highly correlated with broadband provision. A statistically significant relationship exists between broadband and establishments, but the intensity of this depends on firm size and industry.…”
Section: Fixed and Mobile Ict Infrastructure In Contextmentioning
confidence: 99%
“…The inputs utilized for benchmarking ZIP code areas within the broadband core are displayed in Table 2 and are largely based on prior confirmatory statistical work that links these variables to broadband provision (Flamm & Chaudhuri, 2007;Grubesic, 2003Grubesic, , 2006Mack & Grubesic, 2009;Prieger, 2003). For example, in the provision of broadband, regions with a higher population are often considered more attractive because they represent a larger pool of potential customers.…”
Section: Data and Resultsmentioning
confidence: 99%
“…broadband) compares to other regions. This type of information is important for regional development efforts as allied agencies attempt to deploy the appropriate mix of resources to attract businesses in an increasing competitive global economy (Gulati, Nohria, & Zaheer, 2000;Mack & Grubesic, 2009). As the results of this paper indicate, the use of DEA allows one to benchmark regional performance in attracting broadband provision-providing a more complete picture of regional status and competitiveness.…”
Section: Local Efficiency Clustermentioning
confidence: 88%
See 2 more Smart Citations